Ranking European regions as providers of structural riparian corridors for conservation and management purposes (2013)
Riparian zones are of utmost importance in providing a wide range of ecological and societal services. Among these, their role in maintaining landscape connectivity through ecological corridors for animals and plants is of major interest from a conservation and management perspective. This paper describes a methodology to identify European regions as providers of structural riparian corridors, and to rank them with reference to conservation priority. Physical riparian connectors among core habitat patches are identified through a recent segmentation technique, the Morphological Spatial Pattern Analysis. A multi-scale approach is followed by considering different edge distances to identify core and peripheral habitats for a range of hypothetical species. The ranking is performed using a simple set of indices that take into account the degree of environmental pressure and the presence of land protection schemes. An example for environmental reporting is carried out using European administrative regions and major rivers to summarize indices value. The approach is based on freely available software and simple metrics which can be easily reproduced in a GIS environment.